Development of Learning Media for Earthquake Disaster Through Physics Subjects to Improve Problem Solving Ability and Disaster Preparedness - Rany, T D; Mundilarto, M (Jurnal Pendidikan Fisika Indonesia, 2021)
Intensity of the earthquake disaster in Indonesia is quite high. The impact in the form of casualties and infrastructure damage was very severe. It is very important to teach disaster preparedness knowledge from an early age, including in the field of education. The learning being taught is still glued to the material that has not linked disaster knowledge. The purpose of this research is to produce learning media for earthquake disasters based on android through proper physics subjects to improve problem solving skills and disaster preparedness. The design of this research is R D using the 4D model. The data collection instruments are in the form of expert validation sheets which include media experts and material experts. The research data were collected through observation sheets, questionnaire sheets, and inferential analysis. The results of the development of android-based disaster learning media met the very feasible criteria of 92.1 for media experts and 94.1 for material experts. The Manova test statistical results were 95% for problem-solving skills and 92.7% for disaster preparedness, so it was concluded that Android-based earthquake disaster learning media were used effectively to enhance problem solving skills and disaster preparedness.